Similarities among ectoparasite fauna of sigmodontine rodents: phylogenetic and geographical influences - Cruz, Leonardo Dominici [UNESP]; Fernandes, Fernanda Rodrigues; Linhares, Aricio Xavier (Cambridge University Press, 2012)
Phylogenetic and geographical overlaps in host distributions influence the compositional similarity of ectoparasite fauna in a host-parasite system. In these systems, hosts that are more closely related (phylogenetically) are expected to share more parasitic species than more distantly related hosts. Similarly, hosts sharing a larger geographical distribution overlap are expected to have similar ectoparasites. This study investigated the influence of phylogeny (divergence time) and geographical overlap of some neotropical sigmodontine rodent species on the similarities among their ectoparasite fauna (Mesostigmata and Siphonaptera), using a partial Mantel test. Divergence time was the only significant factor that influenced the similarity among the ectoparasites, when mites and fleas were analysed together. Host species that had diverged more recently displayed ectoparasite fauna that were similar. The similarities of the flea species showed similar results in both separate and joint analyses, but neither phylogenetic nor geographical overlap influenced the similarity in mite species. Fleas were shown to be more host-specific than were mesostigmate mites, probably because of the increased influence of host phylogeny.
Keywords: flea; geographical overlap; mammal; mite; phylogeny